Embracing the Wave: The Disruption of Conversational Artificial Intelligence toward English for Specific Purposes (ESP) Teaching Transformation - Ningsih, Nurfajri; Lenon, Samantha Sahara; Rahman, Patur (ETERNAL (English, Teaching, Learning, and Research Journal), 2023)
atGPT, a state-of-the-art artificial intelligence (AI) chatbot which is intended to have natural, intuitive human-to-human conversations by employing cutting-edge machine learning algorithms to produce responses to text input that resemble those of a human, is altering the teaching process especially in English for specific purposes (ESP). It engages learners on multiple cognitive levels, reinforcing comprehension and retention of ESP concepts. However, as we embark on this transformative journey, the potential displacement of human educators is needed to be concerned since AI is able to take over the teacher roles. This paper provides a comprehensive exploration about the benefits and challenges from the disruption of ChatGPT toward teachers’ teaching practice, especially for teachers who deliver English material for certain professional purposes. The study employs library research method design to identify sources that offer accurate data or professional judgment regarding a research question; eventually, these sources are a prerequisite for all other research techniques. The research has clearly described not the benefits of involving ChatGPT in teaching and learning transformation but also the advantages to enhance teachers’ abilities in delivering ESP content. However, there are some disruptions which become a big challenge in this paper which needs to be concerned by teachers and students. Overall, the challenges of ChatGPT involvement in teaching ESP emphasized that even though ChatGPT is sophisticated enough to facilitate learning and teaching environment, teachers’ role is still irreplaceable.